2003
DOI: 10.1046/j.1469-8137.2003.00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic irradiance signalling in tobacco

Abstract: Summary• We report the influence of a systemic irradiance signal, from mature leaves, on the anatomical characteristics of developing leaves.• A systemic signal of reduced irradiance was induced by growing tobacco ( Nicotiana tabaccum ) plants at high irradiance and then measuring the effect of shading mature leaves on the development of new leaves. The reverse, a systemic signal of increased irradiance was induced by growing plants at low irradiance and then measuring the effect of increasing the irradiance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
98
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 20 publications
5
98
0
2
Order By: Relevance
“…It is well known that stomatal morphogenesis is controlled by genetic as well as environmental factors and in general, an increase in light intensity results in an increase in stomatal index and a systemic signal from mature leaves determine the response. 43,[75][76][77][78] Light is perceived by various photoreceptors, 79,80 and stomatal movements are regulated by both blue and red light.…”
Section: Light Regulation Of Stomatal Movementmentioning
confidence: 99%
“…It is well known that stomatal morphogenesis is controlled by genetic as well as environmental factors and in general, an increase in light intensity results in an increase in stomatal index and a systemic signal from mature leaves determine the response. 43,[75][76][77][78] Light is perceived by various photoreceptors, 79,80 and stomatal movements are regulated by both blue and red light.…”
Section: Light Regulation Of Stomatal Movementmentioning
confidence: 99%
“…Larger top canopy leaves generally take advantage of the higher irradiance by exposing a larger surface to sun. In tobacco, leaves tended to be small under low irradiance; leaf size increased with irradiance until a certain level was reached [61].…”
Section: Relationships Between Leaf Morphology and Height In The Canopymentioning
confidence: 99%
“…Since then, some studies have reported that stomatal density, leaf thickness, and the development of stomatal and palisade tissue in newly developed leaves are independent of their local irradiance in Arabidopsis, poplar (Populus spp. ), and tobacco (Nicotiana tabacum), but instead depend on the light environment of mature leaves (Lake et al, 2001;Thomas et al, 2004;Coupe et al, 2006;Miyazawa et al, 2006). This longdistance signal from mature to developing leaves is defined as a systemic irradiance signal.…”
mentioning
confidence: 99%